Iridium-doping as a strategy to realize visible-light absorption and p-type behavior in BaTiO3 - Chandrappa, Sujana (2024)
BaTiO3 (BTO) typically demonstrates a strong n-type character with absorption only in the ultraviolet (λ ≤ 390 nm) region. Extending the applications of BTO to a range of fields necessitates a thorough insight into how to tune its carrier concentration and extend the optical response. Despite significant progress, simultaneously inducing visible-light absorption with a controlled carrier concentration via doping remains challenging. In this work, a p-type BTO with visible-light (λ ≤ 600 nm) absorption is realized via iridium (Ir) doping. Detailed analysis using advanced spectroscopy/microscopy tools revealed mechanistic insights into the n- to p-type transition. The computational electronic structure analysis further corroborated this observation. This complementary data helped establish a correlation between the occupancy and the position of the dopant in the band gap with the carrier concentration. A decrease in the Ti3+ donor-level concentration and the mutually correlated oxygen vacancies upon Ir doping is attributed to the p-type behavior. Due to the formation of Ir3+/Ir4+ in-gap energy levels within the forbidden region, the optical transition can be elicited from or to such levels, resulting in visible-light absorption. This newly developed Ir-doped BTO is a promising semiconductor with imminent applications in solar fuel generation and optoelectronics.